Políticas públicas de saúde e sua relação com o planejamento urbano: estudo de caso da Ocupação Vista Alegre do Juá - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The purpose of this study is the presentation of facts based on literary collections on public health policies and their relationship with urban planning, a case study on the urban occupation Vista Alegre do Juá, presenting the importance of these in a contemporary context and highlighting the population increase in urban areas in the 21st century. It addresses the changes that have arisen in the style and quality of life of the population, which, for lack of choice, are often taken to live in communities of occupation. The objective is to verify the obstacles to the implementation of public health policy in the Vista Alegre neighborhood of Juá. The methodology was based on a case study in order to verify the relationship between public health policies and urban planning. The research techniques used are: bibliographic review, documentary and legislative analysis. The results indicate that there is a need for investments in the locality in public health issues. Finally, it was possible to conclude that access to health for the population of the occupation is precarious, leading to the anonymity of neighborhoods and citizens due to the omission of the responsible public power, which cause in their Basic Health Unit closer overcrowding and often generating inefficient care as well as short of meeting the local need.
Keywords: Ocupação Vista Alegre do Juá; Saúde pública; Planejamento urbano; CNPQ:: CIÊNCIAS DA SAÚDE